People’s Houses as Competition for God’s House in the Book of Haggai - Jadwiga Siewko (Wrocławski Przegląd Teologiczny)
The article aims to characterize the expression people’s houses in the Book of Haggai. This is a novelty against the background of previous publications, which mainly focus on other topics, such as the temple, the figure of the prophet or the background of Haggai’s speech. The starting point is the observation that the author of the book more often refers to the temple by the word bayit than hêkāl. This may indicate a deliberate parallel juxtaposition of people’s houses and God’s house. This parallel juxtaposition creates a wordplay based on the different meanings of the word bayit and may allude to 2 Sam 7. The introduction presents the background that provides the context for Haggai’s speech. First, the results of archaeological research are analyzed to answer the question of what the construction issue was like in Jerusalem at the time of Haggai. Then the rhetorical situation is briefly presented with special attention to the audience to whom the call to rebuild the temple was addressed. The first part analyzes how people’s houses are portrayed in the Book of Haggai itself, without considering references to other books. The second part – how the references in the Book of Haggai to David and Solomon influence the prophet’s message and complement the characterization of the people’s houses. The book repeatedly uses antithesis to show that the attitude of Haggai’s audience is wrong and they should decide to change their behavior. The state of people’s houses is contrasted with the state of God’s house (the temple). Also, the references to David and Solomon are intended to contrast the exemplary attitude of the kings with the bad attitude of Haggai’s audience. All analyses lead to the conclusion that the houses in which people live are in competition with the temple – the house of God.